Gastroschisis annual incidence, mortality, and trends in extreme Southern Brazil - Paulo Acácio Egger; Makcileni Paranho de Souza; Cristiane de Oliveira Riedo; Amanda de Carvalho Dutra; Mariana Teixeira da Silva; Sandra Marisa Pelloso; Maria Dalva de Barros Carvalho (Elsevier, 2022)
Objective: To analyze gastroschisis annual incidence, mortality rates, and trends in the Brazilian state of Rio Grande do Sul from the year 2000 to the year 2017. Method: Population-based study with the analysis of the temporal trend of gastroschisis annual incidence and mortality rates. Data were obtained from the Live Birth Information System and the Mortality Information System, with the analysis performed by polynomial regression modeling. Results: There were 2,612,532 live births, 705 hospitalizations, and 233 deaths due to gastroschisis. The annual incidence of gastroschisis was 2.69 per 10,000 live births. The annual incidence rate increased by 85% in the total period (p = 0.003), and mortality was 33% in the 2000-2017 period. Maternal age < 25 years was a risk factor for gastroschisis (p < 0.001). Children were more likely to be born weighing < 2,500 g (p < 0.001) and with a gestational age < 37 weeks (p < 0.001). The annual incidence trend was to increase, and the mortality trend was to decrease. Conclusion: Similar to what has been described in several regions/countries, there was a trend showing an 85% increase in the annual incidence of gastroschisis (p = 0.003) and the mortality was 33% with a trend of decreasing (p = 0.002).